2021
DOI: 10.1016/j.brs.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Safety of focused ultrasound neuromodulation in humans with temporal lobe epilepsy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 38 publications
(48 reference statements)
2
38
0
Order By: Relevance
“…US only , i.e., US used as a purely neuromodulatory tool, has also been explored in conditions other than AD, including depression, disorders of consciousness, and epilepsy, as well as in healthy individuals, with primary outcome measures including safety and feasibility and, in many instances, constituting proof-of-concept studies and including, for example, EEG recordings and fMR imaging [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. Importantly, most of the studies either reported no adverse events, or sensory responses.…”
Section: Discussionmentioning
confidence: 99%
“…US only , i.e., US used as a purely neuromodulatory tool, has also been explored in conditions other than AD, including depression, disorders of consciousness, and epilepsy, as well as in healthy individuals, with primary outcome measures including safety and feasibility and, in many instances, constituting proof-of-concept studies and including, for example, EEG recordings and fMR imaging [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. Importantly, most of the studies either reported no adverse events, or sensory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary outcomes include changes in seizure frequency, neurological status, neuropsychological profile, and psychological profile. An initial publication from this group reported that among 8 patients who underwent LIFU sonication of the temporal lobe followed by resection of the affected side, no abnormal histological or neuropsychological changes were observed ( 76 ).…”
Section: Fus-mediated Thermal Ablationmentioning
confidence: 99%
“…Most of these human studies provide safety data in the form of neurological examinations and/or structural MRI before and after sonication. Comprehensive reviews also suggest a favorable human safety profile ( 19 , 26 , 41 , 42 ). A recent report ( 41 ) described qualitative safety and side effect assessments in 65 participants who previously completed one or more LIFU experiments.…”
Section: Challenges and Limitationsmentioning
confidence: 99%